If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + 3q = 4 Solving 7p + 3q = 4 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3q' to each side of the equation. 7p + 3q + -3q = 4 + -3q Combine like terms: 3q + -3q = 0 7p + 0 = 4 + -3q 7p = 4 + -3q Divide each side by '7'. p = 0.5714285714 + -0.4285714286q Simplifying p = 0.5714285714 + -0.4285714286q
| -7(5x-3y+5)= | | 17=4-7x-8 | | 3p+4q=26 | | 9w+w+6w= | | 5k-37=11(k+1) | | 71-6v-10v+32=-4v+7 | | (3+6)=3+(6) | | 5x+56+2x+82=180 | | 10v^3=90v | | 4h-7=12h+9 | | -2(5p+3)-3(p-6)= | | 2Y*3Y= | | 4d-5=-5 | | 5x+16+2x+82=180 | | -3x-9=-33 | | 6(2x-5)-4(x+2)-17x= | | 8x+27=5x+63 | | 2c-8=8 | | 16-32-2= | | (8+6)+4=8+(6+4) | | 2y-(-3)=-17 | | -16+-32-2= | | 8x-22=2x+4 | | 2v-(10)=16 | | 4y-5=9y+15 | | 3p-7=6p+8 | | -12m=-18 | | 40-3x-12=44+5x | | -3z-(10)=-17 | | 3x+5=-21-5-x | | 12j^2+11j=-2 | | -2v-(-1)=21 |